Tackling Love Scams: A Review of the Role of the Police in Public Education - Angelia Isabela, Anggraeni; Indarto, Indarto; Halimah, Halimah; Wahyurudhanto, Albertus (Journal of English Language and Education, 2025)
Cybersecurity remains a global problem that can cause major losses worldwide. Technological advances have created new motives for crimes such as love scams. Love scams are frauds that take advantage of emotional relationships to exploit victims for personal gain. The factors causing love scams include the victim's emotional vulnerability, need for attention, and lack of digital literacy. Therefore, it is important for the public to be aware of the various modes of love scams and how to overcome them. This research uses a qualitative method, with data obtained through interviews with 11 sources. Data analysis was carried out through data reduction, data presentation, and data verification. The research results show that, based on Dittipidum data from the Criminal Investigation Department of the Indonesian National Police, there are 18 identified love scam perpetrators with losses reaching 86.3 billion rupiah. Korbinmas Baharkam POLRI has an important role in conducting community development. The steps taken by POLRI include education through socialization, collaborative and community-oriented approaches, and critical intervention and support services. Education that considers the emotional aspect can effectively increase public awareness.